The Disk-Specimen Thickness Does Not Influence the Push-Out Bond Strength Results Between Fiber Post and Root Dentin - Bergoli, Cesar Dalmolin [UNESP]; Amaral, Marina [UNESP]; Valandro, Luiz Felipe (Taylor & Francis Ltd, 2012)
This study evaluated the effect of different thickness of disk-shaped specimens on the push-out bond strength test. Eighteen lower bovine teeth were sectioned (20mm) and prepared (15mm) with the same post system drill (Light Post (R) #1, Schaumburg, IL, Bisco, USA). The apical third of each specimen was embedded in a plastic matrix filled with an acrylic resin (Dencrilay (TM), Dencril, São Paulo, Brazil). The posts were cleaned with alcohol, silanated (ProSil (R), FGM, Joenville, SC, Brazil) and cemented with the RelyX (TM) U100 (3M ESPE, St. Paul, MN, USA). Each specimen was sectioned into three pieces of differing thicknesses (1, 2, and 4 mm). These disk-samples were allocated into 3 groups (n=18) and subjected to push-out testing. One-way ANOVA showed no influence of the specimen thickness on the results (p=0.842). No correlation was observed between thickness and push-out bond strength (Pearson Correlation, r(2)=0.0688; P=0.6209). The push-out bond strength test was not affected by the thickness of the disk-specimens.
Keywords: Fiber post; Push-out bond strength test; Specimen thickness